Manajemen Sarana dan Prasarana Pendidikan Dalam Mendukung Proses Belajar Siswa di SMA Negeri 1 Kuripan - Saputra, Rangga; Najwa, Lu`luin; Irawan, M. Ary (Universitas Pendidikan Mandalika, 2024)
Abstract: The purpose of this study is to describe the management of facilities and infrastructure in improving the learning process at SMA Negeri 1 Kuripan. The research method used is descriptive qualitative. Data collection techniques use observation, interviews, and documentation. Data analysis uses data reduction, data presentation, and conclusion. Based on the results that the author has found at the research location, the management activities of facilities and infrastructure in improving the learning process at SMA Negeri 1 Kuripan consist of 4 focuses, namely: 1) The planning stage which includes analysis of needs, financing, and priorities, 2) The implementation stage is one of the important factors in supporting the smoothness and effectiveness of the teaching and learning process. This can be seen from the suitability of the types of learning media, practice tools, and learning resources with the subject matter and learning objectives, as well as their positive impact on the learning process, 3) Maintenance stage, including two types, namely routine and periodic maintenance 4) Supervision stage, carried out by all stakeholders and without a special supervision team, and carried out periodically. So the conclusion of the study of educational facilities and infrastructure management in supporting the student learning process at SMA Negeri 1 Kuripan is that carrying out the planning, implementation, maintenance, and supervision processes, thus can have a positive impact on the learning process and improving the quality of learning, student learning interest, and achievement of learning achievements.Keywords: Management of Facilities and Infrastructure, Learning Process.Abstrak: Tujuan penelitian adalah untuk mendeskripsikan manajemen sarana dan prasarana dalam meningkatkan proses pembelajaran di SMA Negeri 1 Kuripan. Metode penelitian yang digunakan adalah deskriptif kualitatif. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Analisis data menggunakan reduksi data, penyajian data dan penarikan kesimpulan. Berdasarkan hasil yang telah penulis temukan di lokasi penelitian, kegiatan manajemen sarana dan prasarana dalam meningkatkan proses pembelajaran di SMA Negeri 1 Kuripan terdiri dari 4 fokus, yakni: 1) Tahap perencanaan yang meliputi analisis kebutuhan, pembiayaan, dan prioritas, 2) Tahap pelaksanaan merupakan salah satu faktor penting dalam mendukung kelancaran dan efektivitas proses belajar mengajar. Hal ini terlihat dari kesesuaian jenis media pembelajaran, alat praktik, dan sumber belajar dengan materi pelajaran dan tujuan pembelajaran, serta dampak positifnya terhadap proses pembelajaran, 3) Tahap pemeliharaan, meliputi dua jenis yaitu pemeliharaan rutin dan berkala 4) Tahap pengawasan, dilaksanakan oleh semua stakeholder dan tanpa adanya tim khusus pengawasan, dan dilaksanakan secara berkala. Maka kesimpulan dari penelitian manajemen sarana dan prasarana pendidikan dalam mendukung proses belajar siswa di SMA Negeri 1 Kuripan yaitu dengan melakukan proses perencanaan, pelaksanaan, pemeliharaan, dan pengawasan, dengan demikian hal ini dapat memberikan dampak positif terhadap proses pembelajaran seperti peningkatan kualitas pembelajaran, minat belajar siswa, dan pencapaian prestasi belajar.Kata kunci: Manajemen Sarana dan Prasarana, Proses PembelajaranÂ